Development of Game-Based Learning Media on Islamic Religious Education Materials - Muhammad Zainuddin; Mardianto Mardianto; Hasan Matsum (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
This study aimed to determine the level of feasibility, practicality, and effectiveness of game application learning media on Islamic Religious Education materials. The research method used is the Research and Development (R&D) approach of Brog and Gall mode. The subjects in this study were students of class X MAS al-Washliyah Stabat, while the object of this research was the development of game-based learning media. The data collection instruments used were observation and questionnaires. The results showed that the feasibility level of game application learning media according to material experts was categorized as valid with a score of 86, media experts were categorized as very valid with a score of 91 and linguists were also categorized as valid with a score of 83 so that a cumulative score of 86.7 was obtained with a valid category. The level of practicality of the game application learning media was carried out to 20 students of class X on the learning material of aqidah morals who were experts in the field of Islamic education, the results obtained were responses in the use of media with honest method that was beautiful as a form of application of the commendable nature contained in the moral material obtained a score of 94,2. For the development of effective application-based learning media from the application of this game media, namely, the material presented is easier to understand, teachers from the schools studied also considered this media suitable to be applied because it is more practical.